Business model development of experience economy using Chinese escape room as a simulation - Xiufeng, Ye; Wisedsind, Noppawan; Naknok, Sakchai (Edelweiss Applied Science and Technology, 2025)
This study explores the development of the business model of Chinese-style escape rooms within the context of the experience economy. The aim is to understand how factors such as product construction, communication strategies, derivative development, customer experience, and value interact to shape the success of escape rooms in China. The objective is to provide a comprehensive analysis by combining quantitative and qualitative research methods. A mixed-methods approach was used, including customer surveys (n = 600) and semi-structured interviews with industry professionals (n = 10). Quantitative data were analyzed through descriptive statistics, correlation, and regression analysis, while qualitative data were analyzed using thematic analysis. Findings show that product construction, communication strategies, and derivative development significantly influence customer experience and perceived value. Regression results reveal strong positive relationships, with product design and communication strategies having the greatest impact on customer outcomes. Qualitative insights further emphasize the importance of immersive experiences, customer engagement, and innovation in adapting to market trends. Chinese escape rooms' business models should prioritize high-quality design, effective marketing, and the development of derivative products to enhance customer satisfaction and loyalty. The novelty of this study lies in its integration of the experience economy framework with a focus on the escape room industry, offering new insights for businesses in the entertainment sector.